(untitled) (Academicia Globe: Inderscience Research, 2022)
The article is devoted to the study of neologisms in the Russian language, which are widely used in Internet communication. The article considers the In ternet as a special communicative environment in which the language is undergoing changes. New phenomena that appear on the web need to be named. The nomination process can take place in two ways: the formation of new words, as well as the emergence of new meanings for words. The study of Internet vocabulary is an urgent problem for the modern Russian language. The author made an attempt to summarize new material on the topic under study, to analyze the lexical units selected during the study of Internet discourse in Russian. The paper considers the factors influencing the formation of Internet neologisms, identifies a number of their lexico-semantic groups. The conclusion is made about the inevitability of changes in the word-formation system of the Russian language, which occur under the influence of the Internet environment in the context of the globalization of the language space.